Characterization Of Pure and Immobilized Invertase Enzyme Using Activated Carbon - Dahlia Rosma Indah; Husnul Hatimah (Universitas Pendidikan Mandalika, 2023)
This research is conducted to determine the optimum pH, the optimum temperature, the optimum incubation time, Km and Vmaks enzym invertase mobile and immobile. The research variable are the characteristic of enzym invertase mobile and immobile that include the optimum pH, the optimum temperature, the optimum incubation time, Km, Vmaks and the activity of enzym. The instrument of the research is spectronic UV-Vis. The result of the research are absorbance value and henceforth that will be substituted into the similarity of standart liquid invert sugar in regretion curva, from this procedure the researcher find the concentration’s product (invert sugar). This concentration value will be used for determining enzym activities. The data are collected then analyzed by using descriptive method that use a corelation graph between enzym activity and research variable.The result of the research shows that enzym invertase mobile have optimum pH 4.5, optimum temperature 55°C; optimum incubation time 25 minute; Km value 1,279 mg/mL (4,737 x 10-6 mol/L) and Vmaks value 23,256 mg/mL/menit. The enzym invertase immobile have optimum pH 4; optimum temperature 60°C; optimum incubation time 30 minute; Km value 2,255 mg/mL (8,352 x 10-6 mol/L) and Vmaks value 19,608 mg/mL/minute.